KINERJA VENTILASI PADA HUNIAN RUMAH SUSUN DUPAK BANGUNREJO SURABAYA - C. Indrani, Hedy; , (Institute of Research and Community Outreach - Petra Christian University, 2008)
Natural ventilation for dwellings in tropical wet regions is very important for health. The requirement for natural ventilation is measured in air change rate (ACH) constituting of the availability of fresh air, quality of air circulation, heat losses, and unwanted gasses in the room. Wind speed is useful for accelerating evaporative cooling process and thus plays an important role for thermal comfort in the interior room. Local wind conditions affects the ventilation of a building and therefore might cause problems in predicting the natural ventilation and thermal comfort in a high-rise building, especially in the area and orientation of an opening that is not perpendicular to the wind direction. Ventilation parameters that are to be observed are the air flow rate and air change (ACH) that are gained from a simulation using the AILOS software. The results show that if the opening orientation is at the wind shadow zone, the interior space will not receive wind, it obtains sucking pressure instead. The design of an opening should focus on the area of inlet and outlet because when ACH does not increase, consequently internal wind speed becomes low and thermal comfort will not be met. Abstract in Bahasa Indonesia: Keberadaan ventilasi alam pada hunian lingkungan tropis lembab sangat penting bagi kesehatan. Persyaratan ventilasi alam dinyatakan dalam bentuk air change rate (ACH) berupa ketersediaan udara segar, sirkulasi udara yang baik, pengeluaran panas, dan gas yang tidak diinginkan di dalam ruang. Kecepatan angin bermanfaat mempercepat proses evaporative cooling, sehingga sangat berperan dalam menciptakan kenyamanan termal ruang dalam. Kondisi angin setempat mempengaruhi lingkungan penghawaan suatu bangunan, sehingga mungkin timbul permasalahan dalam memprediksi kondisi ventilasi alam dan kenyamanan termal pada hunian rumah susun, utamanya luasan dan orientasi bukaan yang tidak tegak lurus aliran angin. Parameter ventilasi yang akan diamati yaitu air flow rate dan air change (ACH) yang didapatkan dari simulasi dengan menggunakan perangkat lunak AILOS. Hasil menunjukkan bahwa jika orientasi bukaan berada pada wilayah wind shadow maka ruang dalam tidak menerima angin, yang terjadi justru mendapat tekanan hisapan. Desain bukaan perlu memperhatikan luasan inlet dan outlet karena apabila ACH tidak mengalami kenaikan berarti, maka kecepatan angin internal menjadi rendah dan kenyamanan termal tidak terpenuhi. Kata kunci: bukaan, ventilasi alam, kenyamanan termal, rusun di lingkungan tropis lembab.